2023
DOI: 10.1186/s12887-023-04022-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of children under 5 years of age with rotavirus diarrhoea in a hospital setting in Kisangani, DRC, after the introduction of the rotavirus vaccine, a cross-sectional study

Abstract: Background The Democratic Republic of the Congo (DRC) is one of the countries with the highest rotavirus mortality rate in the world. The aim of this study was to describe the clinical features of rotavirus infection after the introduction of rotavirus vaccination of children in the city of Kisangani, DRC. Methods We conducted a cross-sectional study of acute diarrhoea in children under 5 years of age admitted to 4 hospitals in Kisangani, DRC. Rota… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Approximately 10 ml of fecal material was collected in a 20 ml Falcon tube for rotavirus and adenovirus diagnosis using BYOSYNEX adenovirus/rotavirus BSS (Biosynex SA, Illkirch-Graffenstaden, France), a rapid in vitro diagnostic immunochromatographic test. As previously reported, only 50 μl of fecal material was used with the BYOSYNEX adenovirus/rotavirus BSS [ 15 ]. The remaining fecal samples were stored at -20°C for subsequent molecular analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 10 ml of fecal material was collected in a 20 ml Falcon tube for rotavirus and adenovirus diagnosis using BYOSYNEX adenovirus/rotavirus BSS (Biosynex SA, Illkirch-Graffenstaden, France), a rapid in vitro diagnostic immunochromatographic test. As previously reported, only 50 μl of fecal material was used with the BYOSYNEX adenovirus/rotavirus BSS [ 15 ]. The remaining fecal samples were stored at -20°C for subsequent molecular analysis.…”
Section: Methodsmentioning
confidence: 99%
“…These measures, while primarily aimed at curbing the spread of SARS-CoV-2, also affected the transmission dynamics of other infectious agents, including rotavirus. [4][5][6][7] Limited studies have shown that the measures taken to control COVID-19 led to significant reductions in the incidence of rotavirus and other enteric viral infections [8][9][10][11][12][13][14][15] , highlighting the collateral benefits of such public health interventions. However, comprehensive data on changes in the frequency of rotavirus infections before and during the COVID-19 pandemic are still lacking.…”
Section: Introductionmentioning
confidence: 99%